Changing donors improves outcomes of second transplantation in patients who experienced graft failure after first allogeneic stem cell transplantation - Rui Ma; Xiao-Yu Zhu; Yue Lu; Jia Chen; Li Xuan; Hai-Long Yuan; Yang Cao; Wei-Jie Cao; Xiao-Sheng Fang; Kou-Rong Miao; Xiao-Xia Hu; Hai Yi; et al. (Haematologica)
A second transplantation is almost the only salvage for patients encountering graft failure (GF) following the first allogeneic stem cell transplantation. However, there were no standard protocols for second transplantations, and the role of changing donors remained controversial. We retrospectively studied 272 consecutive patients from 18 Chinese centers undergoing second transplantations due to GF, aiming to assess the impact of changing donors and factors affecting second transplantation outcomes. The primary endpoint was neutrophil engraftment. Other endpoints included platelet engraftment, graft versus host disease (GVHD), transplant related mortality (TRM), relapse, and survival. Of the 272 patients, 193 (71.0%) patients experienced primary GF, and 70.6% (192) used a different second donor. Neutrophil engraftment was achieved in 218 (86.3%) patients by d28, and platelet engraftment was achieved in 164 (70.0%) patients by d100. The 3-year cumulative incidence of acute GVHD, chronic GVHD, relapse, and TRM were 43.5%, 27.8%, 15.6%, and 44.6%, respectively. The 1-year and 3-year overall survival (OS) were 56.1% and 49.5%, respectively. Compared to using the same donor, changing donors significantly improved neutrophil (92.4% vs 71.4%, p